Infantile status epilepticus disrupts myelin development - Bencurova, Petra; Laakso, Hanne; Salo, Raimo A; Paasonen, Ekaterina; Manninen, Eppu; Paasonen, Jaakko; Michaeli, Shalom; Mangia, Silvia; Bares, Martin; Brazdil, Milan; Kubova, Hana; Gröhn, Olli (Neurobiology of disease, 2022)
Temporal lobe epilepsy (TLE) is the most prevalent type of epilepsy in adults; it often starts in infancy or early childhood. Although TLE is primarily considered to be a grey matter pathology, a growing body of evidence links this disease with white matter abnormalities. In this study, we explore the impact of TLE onset and progression in the immature brain on white matter integrity and development utilising the rat model of Li-pilocarpine-induced TLE at the 12th postnatal day (P). Diffusion tensor imaging (DTI) and Black-Gold II histology uncovered disruptions in major white matter tracks (corpus callosum, internal and external capsules, and deep cerebral white matter) spreading through the whole brain at P28. These abnormalities were mostly not present any longer at three months after TLE induction, with only limited abnormalities detectable in the external capsule and deep cerebral white matter. Relaxation Along a Fictitious Field in the rotating frame of rank 4 indicated that white matter changes observed at both timepoints, P28 and P72, are consistent with decreased myelin content. The animals affected by TLE-induced white matter abnormalities exhibited increased functional connectivity between the thalamus and medial prefrontal and somatosensory cortex in adulthood. Furthermore, histological analyses of additional animal groups at P15 and P18 showed only mild changes in white matter integrity, suggesting a gradual age-dependent impact of TLE progression. Taken together, TLE progression in the immature brain distorts white matter development with a peak around postnatal day 28, followed by substantial recovery in adulthood. This developmental delay might give rise to cognitive and behavioural comorbidities typical for early-onset TLE.
Keywords: bílá hmota; zobrazování difuzních tenzorů; zvířata; epilepsie temporálního laloku; lidé; myelinová pochva; Diffusion Tensor Imaging; Rats; Status Epilepticus; status epilepticus; předškolní dítě; Adult; Myelin Sheath; krysa rodu Rattus; Humans; Animals; dospělí; Epilepsy, Temporal Lobe; Child, Preschool; White Matter